Is NRXN1 Gene Expression an Important Marker of Treatment of Depressive Disorders? A Pilot Study - Skiba, Aleksandra (J Pers Med, 2021)
Aim: Due to the fact that NRXN1 is associated with neurodevelopmental disorders, the aim of this study was to investigate the role of the NRXN1 gene in the etiology and epigenetics of depression by comparison of NRXN1 mRNA expression and NRXN1 protein level expression in patients suffering from depression versus healthy controls, as well as to search for clinical variables related to expression of the analyzed gene. Material and Methods: A total of 180 people aged 19–64 qualified for the study. The experimental group consisted of 97 people who were psychiatrically hospitalized, diagnosed with recurrent depressive disorders (F33) or who met the diagnostic criteria of a depressive episode (F32) according to ICD-10. The control group included 83 healthy people who volunteered to participate in the study. A sample of peripheral blood was obtained from people who were positively qualified to participate in the study—twice in the experimental group and once in the control group for genetic testing. Sociodemographic variables and data on the course of the disorder were also gathered. Patients were examined on study entry and at the end of the hospitalization with the Hamilton Depression Scale. Obtained data were analyzed statistically. The study was approved by the University’s Bioethics Committee. Results: The gene expression of NRXN1 at both mRNA and protein level significantly differs and it is lower in the experimental group compared to expression in healthy people. The difference in gene expression of NRXN1 at both the mRNA and protein levels between the first and second measurement in the experimental group is also significant. The result demonstrates a higher expression level in the first measurement and lower expression level in the second measurement when reported depression symptoms are less severe. Conclusions: Results concerning expression of NRXN1 may play an important role in further researches about the etiopathogenesis of depressive disorders such as looking for depression biomarkers and identifying evidence which may be relevant to personalize treatment for depression.